Why endurance athletes should avoid fad diets - Kurtz, J. A. (2025)
As endurance athletes, our bodies are finely tuned machines that require proper fuel to perform at their best. One of the mistakes that I see some athletes make is that in the quest for peak performance or ideal body composition, they are tempted to try fad diets promising quick weight loss. While the promises of the quick weight loss and other health benefits promised by these diets can be tempting, they pose risks due to their restrictive or imbalanced approaches. For athletes, in particular, they may fail to provide adequate energy or nutrients to support training and recovery. Therefore, rather than these diets being a shortcut to lower weight and faster times, they can significantly hinder performance, recovery, and overall health, due to one of more of the following shortcomings, all of which are backed by recent research: